The Effect of Training and Placement on the Performance of Aparatur Sipil Negara (ASN) at the DPRD (Dewan Perwakilan Rakyat Daerah) In Seluma Regency - Zuzeta Sundari; Eska Prima Monique Damarsiwi; Nurzam Nurzam (Journal of Indonesian Management, 2021)
This study aims to determine the effect of training and placement on the performance of Civil Servant at the DPRD Office in Seluma Regency. The sample in this study was 35 Civil Servant at the DPRD Office in Seluma Regency. The data Collecting methods used were questionnaires. Analytical methods used are multiple linear regression, determination test and hypothesis testing. The results of the regression analysis show Y = 1.501 + 0.380X1 + 0.603 X2 + e this describes a positive regression direction, meaning that there is a positive effect between X1 (training) and X2 (placement) on performance (Y). It means that if the training and placement variables increase, the performance will increase. The value of the coefficient of determination is 0.590. This means that X1 (training) and X2 (placement) affect performance (Y) by 59% while the remaining 41% is influenced by other variables not examined in this study. The results of the t-test at a significance level of 0.05 explain that Partially, the training and placement variables have a significant effect on the performance of Civil Servant at the DPRD Office in Seluma Regency. The results of the F test at a significance level of 0.05 explain that the training and placement variables have a significant simultaneous effect on the performance of Civil Servant at the DPRD Office in Seluma Regency.